Examining Barriers to Sustained Implementation of School-Wide Prevention Practices. (December 2016) - Turri, Mary G.; Mercer, Sterett H.; McIntosh, Kent; Nese, Rhonda N. T.; Strickland-Cohen, M. Kathleen; Hoselton, Robert
The purpose of this study was to determine if an experimental five-item measure of barriers to implementing and sustaining school-wide prevention practices, the Assessment of Barriers to Implementation and Sustainability in Schools (ABISS), would relate to objective measures of school-wide positive behavioral interventions and supports (SWPBIS) implementation fidelity. The ABISS was administered to individuals in 704 U.S. schools implementing SWPBIS across 11 states, and scores were compared with school demographic variables and SWPBIS fidelity of implementation. Results showed acceptable model fit for the ABISS, partial measurement invariance, and statistically significant relations, after controlling for school demographic variables, with SWPBIS fidelity of implementation, except for schools implementing SWPBIS for 5 or more years. These patterns indicate substantial but decreasing relations of perceived barriers to implementation fidelity as schools continue to implement SWPBIS. Implications are discussed in terms of how assessment of perceived barriers can support implementation and sustainability of school-wide prevention practices.